2019
DOI: 10.1103/physreve.100.042126
|View full text |Cite
|
Sign up to set email alerts
|

Collective performance of a finite-time quantum Otto cycle

Abstract: We study the finite-time effects in a quantum Otto cycle where a collective spin system is used as the working fluid. Starting from a simple one-qubit system we analyze the transition to the limit cycle in the case of a finite-time thermalization. If the system consists of a large sample of independent qubits interacting coherently with the heat bath, the superradiant equilibration is observed. We show that this phenomenon can boost the power of the engine. Mutual interaction of qubits in the working fluid is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 78 publications
(129 reference statements)
0
44
0
Order By: Relevance
“…Some designs of thermal machines using many-body working medium have already been studied in [87,93] where it was reported that collective effects can be beneficial when using non-adiabatic strokes instead of the usual adiabatic ones. Power increase was also pointed out for ensembles of spins 1/2 in [94] where the equilibration speed-up stemming from collective effects allows one to reduce the duration of the cycle, and hence increase the delivered power. Other studies investigate the effect of internal coupling and entanglement between the subsystems constituting the many-body working medium (pair of twolevel systems [7,84], pair of degenerate two-level systems [11], a two-level system coupled to a harmonic oscillator [85,95], and ensemble of spins 1/2 [86]).…”
Section: A Effective Amplificationmentioning
confidence: 85%
See 2 more Smart Citations
“…Some designs of thermal machines using many-body working medium have already been studied in [87,93] where it was reported that collective effects can be beneficial when using non-adiabatic strokes instead of the usual adiabatic ones. Power increase was also pointed out for ensembles of spins 1/2 in [94] where the equilibration speed-up stemming from collective effects allows one to reduce the duration of the cycle, and hence increase the delivered power. Other studies investigate the effect of internal coupling and entanglement between the subsystems constituting the many-body working medium (pair of twolevel systems [7,84], pair of degenerate two-level systems [11], a two-level system coupled to a harmonic oscillator [85,95], and ensemble of spins 1/2 [86]).…”
Section: A Effective Amplificationmentioning
confidence: 85%
“…Note that we did not take into account the equilibration speed-up emerging form collective effects [94]. This implies that our rough estimate of the equilibration timescale (g 2 τ c ) −1 is probably overestimating the actual equilibration time.…”
Section: Appendix G: Effective Amplificationmentioning
confidence: 97%
See 1 more Smart Citation
“…In this case, the time-dependent currents in the second law will have to be calculated numerically. We expect our findings to be relevant for systems that are coupled to reservoirs only for a finite time, e.g., in finite time thermodynamic cycles [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ], where the coarse-graining dissipator is a more appropriate choice for finite-time dissipative strokes than the usual BMS limit.…”
Section: Discussionmentioning
confidence: 87%
“…With the renewed interest in quantum thermodynamics, it has become a relevant question whether QPTs can be put to use e.g. as working fluids of quantum heat engines [11][12][13][14]. This opens another broad research area of dissipative QPTs in non-equilibrium setups.…”
Section: Introductionmentioning
confidence: 99%